Pengaruh Hak Merek Terhadap Strategi Pemasaran Dan Diferensiasi Produk Di Indonesia - Andini Permatasari; Rizka Ari Agustin; Dimas Aditya (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
In a business, there must be characteristics of each business actor so that legal protection can be given to the works they sell. Physically, the work or product must have a differentiator from the products of other business actors in order to avoid disputes. This literature article will examine the effect of trademark rights on marketing strategies and product differentiation in Indonesia. It will certainly provide results on the level of effectiveness of the marketing strategy by maximizing the concept of product differentiation. Therefore, of course it has factors that influence Trademark Rights on Marketing Strategy and Product Differentiation.